The kinematic analysis on Thomas Enqvist's forehand topspin technique - Guo, J.; Zhou, J.; Wang, H. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
This paper presents knowledge on kinematic feature of an outstanding athlete who uses forehand topspin technique during a tennis match. Thomas Enqvist had used forehand topspin technique to receive for three times in the ATP Championship Round-robin Tournament Semifinal, which was held in Chengdu, China. The technique of forehand topspin has been further analyzed by three-dimensional video. Through study, the kinematic technical feature has been obtained, resulting in not only providing referential statistics for the technical training of the athletes, but also enriching the technical theory of tennis.